KNOWLEDGE IMPROVEMENT AND BEHAVIOR CHANGE IN THE NEW NORMAL ERA IN STUDENTS OF SMPN 01 RENGAT BARAT - Deswita Deswita; Novita Kusumarini (Poltekkes Kemenkes Riau, 2022)
The rapid development of the corona virus infection has finally spread throughout the world quickly which is suspected to be transmitted through direct contact with sufferers, through goods and other media, making this epidemic finally unable to suppress its spread. For this reason, it is necessary to inculcate the habit of using health protocols in the New Normal Era, with the hope that the community, including students at schools, are able to carry out health protocols in everyday life both at home and at school. SMPN 01 is one of the schools that enforces the implementation of health protocols during the pandemic. However, based on observations, there are still many students who have not implemented health protocols properly, for that a covid task force was formed to assist in supervising the implementation of health protocols in schools. The purpose of this activity is: to increase knowledge and change the behavior of students of SMPN 01 Rengat Barat in implementing health protocols.